A world apart global inequality and its consequences - Films For The Humanities & Sciences (Firm) (Hamilton, NJ : Films for the Humanities & Sciences, 2008)
A growing number of environmentalists, ethicists, and economists believe that the needs of the'have-nots' will one day become too powerful to ignore. This program highlights that viewpoint, illustrating vast disparities between the living standards of developed and underdeveloped nations and questioning the wisdom of looking the other way
DVD format
Keywords: Poverty -- Africa; Illegal arms transfers -- Africa; Female infanticide -- India